2020
DOI: 10.37033/fjc.v5i1.146
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Properties of Nutmeg (Myristica fragrans houtt) of North Sulawesi Nutmeg

Abstract: Essential oil of nutmeg (Myristica fragrans houtt) is one of the many potentials of nutmeg that has a high economic value although in North Sulawesi it has not been exploited to its full potential. This research was conducted to compare the yield and properties of Nutmeg oil extract from the seeds and mace of Talaud and North Minahasa-North Sulawesi. The oil extract was obtained by distillation and was further characterized in terms of color, solubility in ethanol, density, optical rotation, refractive index. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…It is suggested that the phenolics compounds, which are antioxidants, are responsible for the antibacterial activity. Experimentally, brownish colour was formed after the extract addition to Folin-Ciocalteu reagent and 2% Na2CO3, as can be seen in figure (4) indicating a good phenolic content compared with standard gallic acid…”
Section: Total Phenolic Contentsmentioning
confidence: 92%
See 2 more Smart Citations
“…It is suggested that the phenolics compounds, which are antioxidants, are responsible for the antibacterial activity. Experimentally, brownish colour was formed after the extract addition to Folin-Ciocalteu reagent and 2% Na2CO3, as can be seen in figure (4) indicating a good phenolic content compared with standard gallic acid…”
Section: Total Phenolic Contentsmentioning
confidence: 92%
“…The trace elements that exist in nutmeg extract is displayed in the table (4), which specify the presence of Cu, Zn, Pb, Cr, Ni, and Mn in the concentration of 150, 280, 6.1, 0.08, 0.09, 0.0012, and 0.027 µg/dl, respectively. These elements are considered essential to human health.…”
Section: Content Of Trace Elements In Nutmeg Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…Myristica fragrans Houtt. or nutmeg is an indigenous plant of Indonesia (Ibrahim et al, 2020;Rahardiyan et al, 2020). It has been cultivated in many tropical countries such as Malaysia, India, Indonesia, Grenada, Mauritius, Singapore, Sri Lanka, and many African countries (Al-Rawi et al, 2011;Kuete, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…is a native Indonesian plant, which originated from Banda Island and grows effectively in the tropics (Bermawie et al, 2018). It is also known as a spice plant with high economic value and multipurpose, because every part it is used in various industries (Rahardiyan et al, 2020). Nutmeg is known to have antimicrobial activity as showed by Nurhasanah (2014), against pathogenic bacteria, such as Staphylococcus aureus and Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%